2018
DOI: 10.4274/tjod.48091
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin as a predictor for growth of fetus and infant

Abstract: Objective:Visfatin is an adipocytokine that functions as an enzyme and a growth factor to investigate the relationship between serum visfatin and the fetus’s anthropometric markers up to a year after birth.Materials and Methods:Forty-one eligible pregnant women in their first trimester were divided and matched in terms of body mass index (BMI) before pregnancy into normal and higher than normal BMI groups, A and B. Serum visfatin levels were measured during 6-12 and 15-20 weeks of gestation using ELISA.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A positive correlation of its concentration with neonatal birth weight has been observed by Mazaki-Tovi et al [ 100 ]. Taraqi et al, in turn, found a negative correlation between visfatin levels and infants’ birth weight whose mothers had a BMI higher than normal [ 101 ].…”
Section: Biomoleculesmentioning
confidence: 99%
“…A positive correlation of its concentration with neonatal birth weight has been observed by Mazaki-Tovi et al [ 100 ]. Taraqi et al, in turn, found a negative correlation between visfatin levels and infants’ birth weight whose mothers had a BMI higher than normal [ 101 ].…”
Section: Biomoleculesmentioning
confidence: 99%
“…Another study positively correlated umbilical cord visfatin levels with fetal birth weight, indicating its potential role in fetal growth regulation [ 105 ]. Taraqi et al found an inverse correlation between visfatin levels and birth weight in patients with higher than normal BMI [ 106 ]. Furthermore, higher levels of this protein were associated with IUGR (defined as birth weight ≤ 3rd customized centile), especially during the third trimester of pregnancy [ 107 , 108 ].…”
Section: Clinical Applications Of Adipokines Measurements In Variomentioning
confidence: 99%
“…In our study, a positive correlation was found between visfatin levels and fetal anthropometric parameters, such as weight, length, and head circumference at birth. Mashhad Taraqi & Tehranian (2018) showed an influence of maternal BMI on the correlation between visfatin levels throughout pregnancy and fetal parameters such as weight, length, and head circumference at birth. Furthermore, an association has been reported between serum visfatin levels in the first trimester of pregnancy and final birth weight (Valsamakis et al, 2014).…”
Section: Discussionmentioning
confidence: 99%